Low Carbohydrate Diet (SCD/GAPS) for Children with Autistic Spectrum Disorder - Abele, Silvija; Tzivian, Lilian; Meija, Laila; Folkmanis, Valdis (International society for nutritional psychiatry research (ISNPR) conference, London, United Kingdom, 20-22 October 2019, 2019)
Objective of the study was to investigate the potential of low carbohydrate diet (SCD/ and supplements in reducing some autistic spectrum disorder ASD symptoms in children.
Keywords: Autism spectrum disorder (ASD); Gluten Free diet; Casein Free diet; Low carbohydrate diet; Children with autism spectrum disorder; Research Subject Categories::MEDICINE::Social medicine